The Effect of Paired Conversation Activity by Utilizing News-Based Materials in Improving the Students’ Speaking Skill - Khadijah Maming; Raya Mangsi (Universitas Sulawesi Barat, 2019)
The objective of this study focused on the effect of paired conversation activity by utilizing news-based materials in improving the students’ speaking skill. The students were supposed to comprehend the content of news-based materials and then explain and conclude the essential things from the news orally. It was focused on improving the students’ productive skill that is speaking skill. This research covered different topics of news taken from some resources such as; international yahoo news, BBC news, YouTube, magazine, and other mass media. In this research, the students also be expected to search and discover the course materials by themselves from internet, television etc. They discussed the topics of news-based materials with his/her pair. They started to discuss the news by using W-H questions, namely; who, what, where, why, when, and how. The lecturer has role as facilitator and consultant of the students in learning. It involved several learning activities, such as; preparing the news-based materials taken from BBC news, international yahoo news, magazine, etc, making group in pair, reading carefully the news-based materials, discussing the essential things from the news, conclude the news orally, and presenting in front of the class. This study was experimental research design and applied quantitative method. The students of English Education Study Program of Muhammadiyah University of Parepare taken as the subject of this research. They were taught speaking course through the implementation of paired conversation activity by utilizing news-based materials. Through this treatment, it was found out that paired conversation activity by utilizing news-based materials has good effects in improving the students’ speaking skill. Besides, the students also gave positive responses toward the application of paired conversation activity by utilizing news-based material for teaching-learning EFL speaking. This technique allows the students got the good opportunity to speak at length and helps them to develop their oral language proficiency.